Genome-wide association studies of cerebral white matter lesion burden: the CHARGE Consortium - Fornage, Myriam (2011)
OBJECTIVE: White matter hyperintensities (WMH) detectable by magnetic resonance imaging (MRI)are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMH are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWAS) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs)in one locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (P(discovery)= 4.0×10(−9); P(replication) =1.3×10(−7); P(combined) =4.0×10(−15)). Other SNPs in this region also reaching genome-wide significance are rs9894383 (P=5.3×10(−9)), rs11869977 (P=5.7×10(−9)), rs936393 (P=6.8×10(−9)), rs3744017 (P=7.3×10(−9)), and rs1055129 (P=4.1×10(−8)). Variant alleles at these loci conferred a small increase in WMH burden (4–8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.